Central nervous system: re-establishing lost connections - DanielSteffi; ClarkAbbot F.; McDowellColleen M. (眼科学报, 2016)
In the July issue of Nature Neuroscience , Lim et al. published their study on regeneration of target-specific retinal ganglion cell (RGC) axons by enhancing visual activity and intrinsic signaling pathways after optic nerve crush (ONC) injury (1,2). This study provides promising data to support the notion that adult neurons of the central nervous system